Analisis Kebijakan Pengembangan Ekowisata Berbasis Masyarakat di Dermaga Kereng Bangkirai: Tinjauan Regulasi, Partisipasi Komonitas dan Pelestarian Ekosistem Gambut Sabangau - Varel Varel; Christian Veraldo Nugroho; Elia Wulandari; Orda Sasa (Lembaga Pengembangan Kinerja Dosen, 2026)
The post-pandemic recovery of Indonesia's tourism sector has spurred a significant shift towards sustainable tourism, establishing Community-Based Ecotourism (CBET) as a vital approach for high-value conservation areas. This research analyzes CBET policy development at Dermaga Kereng Bangkirai, Palangka Raya, Central Kalimantan, by integrating three dimensions: the effectiveness of local government regulations, community participation via Pokdarwis, and the ecological implications for the Sebangau National Park peatland ecosystem. Utilizing a qualitative library research method, the study synthesizes secondary data including regulations, accredited journals, and official reports from 2020–2026 through content and thematic analysis. Findings reveal three structural challenges: regulatory disharmony between local revenue targets and national conservation mandates; CBET participation remaining in a transitional phase where Pokdarwis involvement is limited to pragmatic economic interests; and latent ecological threats, such as hydrocarbon pollution and habitat disturbance, arising from insufficient mitigation instruments. The study highlights the urgent need for integrated policy engineering that harmonizes tourism, community empowerment, and peatland ecosystem preservation. These findings provide a strategic framework for stakeholders, ultimately contributing to the achievement of Sustainable Development Goals (SDG) 8 and SDG 15.